Analisis Implementasi Metode Drill dengan Tutor Sebaya dalam Mengembangkan Kemampuan Kognitif Matematis Siswa Di Sekolah Dasar - Putri Dwi Fatmawati; Jamilatun Nafi'ah (Supermat : Jurnal Pendidikan Matematika, 2026)
Learning mathematics in elementary school often presents difficulties because many students still struggle to understand multiplication, a concept that requires both procedural skills and automatic recall. This study explores how the Drill method combined with peer tutoring was applied in the classroom, how interactions among students supported the memorization process, and how these activities contributed to the development of their cognitive abilities. The research used a qualitative case study design involving 37 students and a classroom teacher as an additional informant, with data gathered through observation, interviews, and documentation. The analysis followed the Miles and Huberman model through stages of reducing data, organizing it, and drawing conclusions. The results show that the Drill activities supported by peer tutors were carried out in a structured pattern of repeated practice, alternating checking, and teacher supervision, leading to improvements in students’ thinking speed, accuracy in recalling multiplication facts, and ability to respond quickly. Consistent application of this method strengthened students’ multiplication mastery, and the study highlights its value as a simple yet effective approach for large classes while offering teachers an alternative strategy to enhance students’ cognitive skills through a mix of intensive practice and social support.